2019
DOI: 10.1186/s12992-019-0530-6
|View full text |Cite
|
Sign up to set email alerts
|

Building the capacity of users and producers of evidence in health policy and systems research for better control of endemic diseases in Nigeria: a situational analysis

Abstract: BackgroundThere is a current need to build the capacity of Health Policy and Systems Research + Analysis (HPSR+A) in low and middle-income countries (LMICs) as this enhances the processes of decision-making at all levels of the health system. This paper provides information on the HPSR+A knowledge and practice among producers and users of evidence in priority setting for HPSR+A regarding control of endemic diseases in two states in Nigeria. It also highlights the HPSR+A capacity building needs and intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The finding that although many of the policy/decisionmakers were knowledgeable that research evidence should inform policy decisions but only a few reported they are currently using/have ever used in the past for developing policy/strategy and implementation or reviewing programs shows that high knowledge or awareness of HPSR does not translate to policy and practice. Our finding is in line with other studies that reported limited use of evidence in decision-making (18,37), and in contrast with another study that found knowledge to translate to evidence use (4).…”
Section: Discussionsupporting
confidence: 92%
“…The finding that although many of the policy/decisionmakers were knowledgeable that research evidence should inform policy decisions but only a few reported they are currently using/have ever used in the past for developing policy/strategy and implementation or reviewing programs shows that high knowledge or awareness of HPSR does not translate to policy and practice. Our finding is in line with other studies that reported limited use of evidence in decision-making (18,37), and in contrast with another study that found knowledge to translate to evidence use (4).…”
Section: Discussionsupporting
confidence: 92%
“…Although funding and implementation are essential in primary healthcare systems across states in Nigeria, various challenges may hinder complete and optimal implementation, considering that it is in a nascent stage. The existing literature on the BHCPF has only explored topical issues on the political economy of its design, 7,[22][23][24][25][26] accountability mechanisms, 25 status of fund release and execution at the national level, 7,27 and broader health nancing landscape assessments. 28 These literature had provided valuable insights into the structural and procedural aspects of the BHCPF.…”
Section: Rationalementioning
confidence: 99%
“…This approach is crucial for bridging the gap between research and policy implementation, facilitating evidenceinformed decision-making. Onwujekwe et al (2019) further reveal the disparity between the awareness and actual use of health policy and systems research (HPSR) evidence in policymaking, indicating a need for empowering decisionmakers with the autonomy to utilize evidence effectively. Dada et al (2022) demonstrate the practical application of these principles through their work in building a responsive healthcare system in Nigeria.…”
Section: Implications For Policy and Practice In Enhancing Healthcare...mentioning
confidence: 99%